China's Belt and Road Initiative: Perspectives from India. Issue 5 (September 2017) - Jacob, Jabin T.
Abstract: China's Belt and Road Initiative (BRI) is often simplistically understood as being opposed by India and supported by Pakistan. The reality on the ground is rather more complex. The emerging consensus in India appears to be that, far from being exclusively an economic and infrastructure development program, the BRI may be understood as a long‐term strategic initiative that seeks to convert China's current economic might into diplomatic influence. While attempts have been made by Beijing, the reflexive Indian suspicion of Chinese international projection, including of China's BRI, has not yet been met by a coherent discourse designed to specifically address Indian concerns. In contrast, in Pakistan, widespread acceptance of the importance and necessity of the China–Pakistan Economic Corridor is increasingly coupled with concerns within sectors of Pakistani society over the fairness, transparency and eventual economic outcomes of the project. Accordingly, this paper is divided into two parts: the first looks at how Indian analysts have viewed and responded to the Chinese discourse and arguments on the BRI; the second considers the debate over the China–Pakistan Economic Corridor within Pakistan.